The Parental Emotional Support and Self-Confidence on Interest In Choosing A College Major in Psychology Students - Alisin, Aldi; Uyun, Muhamad (Psychosophia: Journal of Psychology, Religion, and Humanity, 2024)
This research aims to determine whether there is a relationship between parental emotional support and self-confidence and the alignment of interests of psychology students. The type of research used is quantitative. The sampling technique used simple random sampling with a total of 197 active psychology students, class of 2023 in UIN Raden Fatah Palembang as subjects. This research used data analysis methods which are used to test research hypotheses using multiple linear regression tests. The results of the major hypothesis test show that the F value is 24.619 with a significant value of 0.000. So, it can be concluded that simultaneously parental emotional support and self-confidence have a significant influence on the alignment of student interests. The second hypothesis is that the calculated t value is -1.186 < t table value 1.985 with a significance value of 0.237 > 0.05, it means that there is no partial influence between the Emotional Support variable alignment of interests for Students of the Faculty of Psychology UIN Raden Fatah Palembang. The third hypothesis is that the calculated t value is 3.351 > t table value 1.985 with a significant value of 0.000 < 0.05. So, the hypothesis is accepted, which means that there is a partial influence between the Self-Confidence variable in the alignment of interests in Students of the Faculty of Psychology, Class of 2023, UIN Raden Fatah Palembang.